A New Approach Using Modeling to Interpret Measured Changes in Soil Organic Carbon in Forests; The Case of a 200 Year Pine Chronosequence on a Podzolic Soil in Scotland - Ražauskaitė, Rita; Vanguelova, Elena; Cornulier, Thomas; Smith, Pete; Randle, Tim; Smith, Jo U. (Frontiers in Environmental Science, 2020)
Scotland is continuing to afforest land in order to combat climate change, but the long-term capacity for carbon sequestration in forest soils is still uncertain. Soil organic carbon stock changes were studied in a >120 year-old Scots pine chronosequence and adjacent grassland sites on podzolic soils. Significant differences were observed in the top organic soil horizons, while no changes were noted in the deeper mineral soil horizons. Simulations with the RothC-26.3 model revealed that pine forests could lose a significant amount of soil organic carbon through management operations. The lowest modelled stocks of soil organic carbon were not in the young sites (0-25 years old), but at 43 years since reforestation. Using measured data from our study site, simulations of grassland afforestation suggested that accumulation of organic carbon under forest is mainly in the organic horizons, while the deeper mineral soil horizons are likely to become depleted in soil organic carbon compared to grasslands. Our simulations suggest that afforestation of grasslands would increase overall soil carbon stocks but deplete the more stable carbon pools in the deeper mineral soils, which is not a desirable outcome in the context of climate change. The measurements provide comparative estimates of SOC in grassland and forestry sites at steady state; few studies provide these comparative measures. This study presents a new method for simulating soils that are accumulating carbon using the assumption of steady state with respect to the rate of accumulation. The approach has never been presented before and could have important implications for estimates of impacts of land use and climate change on the large SOC stocks held in highly organic soils. Subsequent simulations provide a new method for interpolating measurements that allow the losses due to management operations to be determined.